Análise de desempenho de algoritmos criptográficos assimétricos em uma rede veicular (Vanet) - Matos, Leila Buarque Couto de (2013)
This dissertation describes the impact of using asymmetric encryption algorithms, with emphasis on algorithms RSA, ECC and MQQ in scenarios VANET (Vehicular Ad hoc Network). In the research were investigated some simulators as GrooveNet, VANET / DSRC, VANET / CRL Epidemic, NS-2, trans, NCTUns / EstiNET, SUMO, VanetMobiSim and ns-3, suitable for VANET. The algorithms have been implemented in C and inserted into the ns-3, where the simple scenarios created a network VANET. The results showed that it is possible to add protocol-layer security services of vehicular networks (1609.2), these asymmetric algorithms and obtain secure communication between nodes in the VANET.